Exploring the Potential of IoT: An In-Depth Examination of Applications and Prospects - Rao, Allanki Sanyasi; S S, Dr. Sreeja Mole (The journal of contemporary issues in business and government, 2023)
The Internet of Things (IoT) represents a groundbreaking and innovative platform where an intelligent network establishes connections with a multitude of electronic devices via the internet, utilizing existing communication systems to ensure dependable and immediate connectivity. This enables the system to collect data from sensors, process it through computing devices, and trigger actions accordingly. The desire for automation and increased efficiency has played a significant role in driving the progress of this technology. This paper explores the rise of IoT devices and their wide-ranging applications in sectors such as healthcare, agriculture, smart cities, and the driving forces propelling industry advancements and beyond. By scrutinizing these areas, it offers valuable insights into the ever-evolving IoT landscape. Understanding the conditions and forces propelling IoT growth is crucial in comprehending its future trajectory. As the pace of IoT technology evolution accelerates, this paper serves as a comprehensive guide for researchers. It not only provides a thorough analysis of the current IoT landscape but also anticipates potential developments on the horizon. Researchers seeking to contribute to and navigate the dynamic IoT ecosystem will find this paper to be a valuable resource.